Huqıqıy tárbiyanıń jaslar tárbiyasında roli - Yerejepov, M (SCIENCE and SOCIETY, 2024)
The article talks about the concept of legal education, the normative documents adopted in the formation of legal education of schoolchildren and the measures that need to be implemented.
Keywords: right; commitment; education; quality; school; neighborhood; regulatory document; the law; legal consciousness; legal knowledge